2015
DOI: 10.1002/ajmg.a.37377
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in osteogenesis imperfecta: A mixed‐methods systematic review

Abstract: Clinical interventions and research have mostly focused on the orthopedic, genetic, and pharmacological outcomes of individuals with osteogenesis imperfecta (OI), and although quality of life (QoL) has gained recognition as an important patient-outcome, it has received little attention in individuals with OI. This mixed-methods systematic review of the literature included five search engines and identified a total of 212 articles. Once study eligibility was reviewed, 10 studies met the inclusion criteria and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 48 publications
8
69
0
1
Order By: Relevance
“…The studies were appraised by two independent reviewers using the Mixed Methods Appraisal Tool (MMAT) and the CAse REport (CARE) Checklist. Both tools have been previously used in OI reviews (Dahan‐Oliel et al, ; Nghiem et al, ). The MMAT was created for the appraisal stage of complex literature reviews (Hong et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were appraised by two independent reviewers using the Mixed Methods Appraisal Tool (MMAT) and the CAse REport (CARE) Checklist. Both tools have been previously used in OI reviews (Dahan‐Oliel et al, ; Nghiem et al, ). The MMAT was created for the appraisal stage of complex literature reviews (Hong et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the life expectancy of individuals with OI has increased well beyond childhood (Folkestad et al, ). While a number of adults may live a high quality of life for the mental and psychosocial domains (Dahan‐Oliel et al, ), they remain at higher risk of poor physical quality of life. They are also at greater risk of early death; approximately 7–10 years less than the general population (Folkestad, Hald, Canudas‐Romo, et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The theme of enhanced well‐being (renewal), associated with the impact of bisphosphonate therapy, was reported by participants in another study (Tsimicalis et al., ). Dahan‐Oliel, Oliel, Tsimicalis, Montpetit, Rauch, and Dogba () identified that QOL scores increased in children who experienced this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…QOL assessments completed with parents of children with OI describe physical and financial burdens, in addition to social and psychological stressors (Dogba, Rauch, Tre, Glorieux, & Bedos, ; Vanz, Félix, da Rocha, & Schwartz, ). Although physical QOL scores were lower in children and adults with OI; mental and psychosocial QOL scores were the same or better as compared with a well‐population (Dahan‐Oliel et al., ). In contrast Vanz et al.…”
Section: Introductionmentioning
confidence: 97%
“…Opracowano schematy leczenia w zależności od wieku dziecka. Jak wynika z naszych spostrzeżeń, zarówno wcześniejszych jak i przedstawionych w tej pracy, leczenie to systematycznie prowadzi do poprawy stanu zdrowia dziecka [21]. Najwcześniejszymi zauważonymi przez nas efektami były poprawa twardości kości, zmniejszenie ciemienia przedniego i wzrost napię-cia mięśniowego.…”
Section: Dyskusjaunclassified